APLIKASI PENGELOLAAN PENGAJUAN DANA KEGIATAN KESISWAAN DAN LAPORAN PRESTASI SISWA SMK NEGERI 11 BANDUNG - Rochmawati Rochmawati; Agung Anak Agung Gde; Annisa Nurdini Rahmatika; Mochamad Gerda Iqbal Jannaki; Lutfi Alhakim (Jurnal Abdimas Bina Bangsa, 2024)
As a secondary level educational institution, students of SMKN 11 Bandung have various activities. Because of the numerous and varied student activities, manually managing activity submissions is considered inefficient and ineffective. Various problems arise when submissions are made manually. Incompatibility of activities and errors in budget calculation are common mistakes that occur when examining applications. Another problem is that the results of activities are sometimes not properly monitored because the personnel who handle student activities are busy. This problem is the main background for the community service program. In this program, a web-based application was designed, created, and implemented to automate the management of student activity funding applications and generate student achievement reports. Activities start with requirement analysis to mentoring in using the application. Implementation of this application ensures funding applications for student activities and the generation of student achievement reports can be automated